A bimetallic single-atom catalyst for carbon dioxide cycloaddition reaction and preparation method thereof
By supporting bimetallic single-atom catalysts with manganese and zinc on nitrogen-doped carbon materials, the problems of low reaction activity and harsh conditions in the prior art are solved, and the efficient cycloaddition reaction between carbon dioxide and epoxy compounds is achieved. The catalyst is easy to recover and used multiple times and is suitable for a variety of epoxide substrates.
Patent Information
- Application Number
- CN202310571188.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-20
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-05-20
AI Technical Summary
The existing heterogeneous catalysts have low reaction activity and harsh conditions in the cycloaddition reaction of carbon dioxide and epoxy compounds, and are difficult to recover and purify the catalyst, making it difficult to meet the high-efficiency catalytic needs.
Using bimetallic single atom catalyst, nitrogen-doped carbon material derived from zeolite imidazole ester skeleton material is used as a support, and the metal manganese and zinc are supported. It is prepared by high-temperature pyrolysis method, combined with tetrabutylamine bromide as a cocatalyst. The reaction is carried out under pressure to achieve efficient recovery of the catalyst and multiple recycling.
It realizes a high-efficiency cycloaddition reaction between carbon dioxide and epoxy compounds. The catalytic conditions are mild, the yield is high, the catalyst is easy to recover, and has good cycle stability and universality. It is suitable for a variety of epoxide substrates.
Smart Images

Figure CN116713018B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and in particular relates to a bimetallic single-atom catalyst for carbon dioxide cycloaddition reaction and a preparation method thereof. Background Art
[0002] Excessive carbon dioxide emissions have brought ecological and environmental problems to mankind. There are two main effective measures to alleviate this problem: one is to control CO2 emissions from the production pathway, which requires reducing fossil fuel combustion; the other is the subsequent conversion and reuse of CO2, through a series of capture and equipment design, and optimization of the reaction process, to convert carbon dioxide into chemical intermediates or directly into high-value-added chemicals. Among them, the cycloaddition reaction of carbon dioxide and epoxides has attracted much attention because it can convert carbon dioxide under the condition of 100% atomic utilization.
[0003] Cyclic carbonates can be directly obtained by reacting carbon dioxide with epoxy compounds. At present, the catalytic activity of homogeneous catalysts in this field is acceptable, but there are problems such as difficulty in product purification and catalyst recovery. For heterogeneous catalytic application systems, such as porous organic polymers (CN113912805A), MOFs (CN107096569A), carbon materials (CN1149178892A) and ionic liquids (CN106732768A), they can solve problems such as difficulty in product purification and catalyst recovery. However, these heterogeneous catalysts still have shortcomings such as low reaction activity and harsh reaction conditions, which need to be solved urgently. Summary of the invention
[0004] The present invention aims to provide a bimetallic single-atom catalyst for carbon dioxide cycloaddition reaction, which has mild reaction conditions, high reaction activity and excellent cycle stability when used in carbon dioxide cycloaddition reaction.
[0005] The technical solution adopted by the present invention to solve the above problem is: a method for preparing a bimetallic single-atom catalyst for carbon dioxide cycloaddition reaction, comprising the following steps:
[0006] 1) Dissolving zinc nitrate and 2-methylimidazole in methanol respectively to obtain a zinc nitrate methanol solution and a 2-methylimidazole methanol solution respectively, adding the zinc nitrate methanol solution, the 2-methylimidazole methanol solution and a metal precursor acetylacetonate at the same time under stirring at room temperature, stirring at room temperature, centrifuging and washing the obtained product, and vacuum drying to obtain a mixture;
[0007] 2) The mixture is heat treated by high temperature pyrolysis in an inert atmosphere to obtain a bimetallic single atom catalyst.
[0008] Preferably, the stirring time at room temperature in step 1) is 2 to 4 h.
[0009] Preferably, the centrifugal washing and vacuum drying in step 1) are specifically as follows: after centrifugal washing with methanol for 3 times, the three precipitates are combined and placed in a vacuum drying oven at 60° C. for 6 hours to obtain a mixture.
[0010] Preferably, the acetylacetonate in step 1) is manganese acetylacetonate.
[0011] Preferably, the heat treatment temperature in step 2) is 700 ~ 1000 °C.
[0012] Another object of the present invention is to provide a bimetallic single-atom catalyst for carbon dioxide cycloaddition reaction, wherein the bimetallic single-atom catalyst is prepared by using the above-mentioned bimetallic single-atom catalyst for carbon dioxide cycloaddition reaction.
[0013] Preferably, the bimetallic single atom catalyst uses a nitrogen-doped carbon material derived from a zeolite imidazolate framework material ZIF-8 as a carrier, and bimetallic single atoms of metal manganese and zinc as components are loaded on the nitrogen-doped carbon material.
[0014] More preferably, the loading amount of metal manganese single atom on the bimetallic single atom catalyst is 0.09 wt.%.
[0015] More preferably, the loading amount of metallic zinc single atoms on the bimetallic single atom catalyst is 9.1 wt.%.
[0016] Another object of the present invention is to provide an application of a bimetallic single-atom catalyst for carbon dioxide cycloaddition reaction, wherein the bimetallic single-atom catalyst is used as a main catalyst and tetrabutylammonium bromide is used as a co-catalyst, and carbon dioxide and an epoxide are reacted under normal pressure conditions.
[0017] The specific steps include:
[0018] 1) Add bimetallic single atom catalyst, tetrabutylammonium bromide, epoxy compound into the Shrek tube and fill it with carbon dioxide;
[0019] 2) Under normal pressure and temperature of 60 to 90°C, react for 6 to 12 hours;
[0020] 3) Use a filter membrane to separate the catalyst and the reaction product cyclic carbonate. The separated bimetallic single atom catalyst can be reused after washing and drying.
[0021] Preferably, the epoxy compound is any one of propylene oxide, epichlorohydrin, phenyl glycidyl ether, styrene oxide and glycidol.
[0022] Compared with the prior art, the present invention has the advantages of:
[0023] (1) The bimetallic single-atom heterogeneous catalyst for carbon dioxide cycloaddition reaction of the present invention uses a nitrogen-doped carbon material derived from a zeolite imidazolate framework material ZIF-8 as a carrier, utilizes the spatial confinement effect of ZIF-8 to load manganese acetylacetonate, and utilizes the synergistic effect between metallic manganese and zinc to efficiently catalyze the cycloaddition reaction of carbon dioxide and epoxy compounds.
[0024] (2) The bimetallic single-atom catalyst of the present invention is used in the carbon dioxide cycloaddition reaction. The reaction conditions are mild and a high yield can be achieved under normal pressure and solvent-free conditions. The catalyst is easy to recover and can maintain a good catalytic effect after multiple cycles. In addition, it can be used to catalyze a variety of epoxide substrates. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is an electron microscope image of MnZn-NC prepared in Example 1 of the present invention.
[0026] Figure 2 This is a spherical aberration corrected high-angle annular dark field scanning transmission electron microscope HAADF-STEM image of the MnZn-NC prepared in Example 1 of the present invention.
[0027] Figure 3 This is the X-ray diffraction pattern of MnZn-NC prepared in Example 1 of the present invention.
[0028] Figure 4 The performance results of the MnZn-NC prepared in Example 1 of the present invention for catalyzing the cycloaddition of epoxide and carbon dioxide for multiple cycles are shown.
[0029] Figure 5 X-ray photoelectron spectra of Zn 2P orbitals of MnZn-NC prepared in Example 1 of the present invention, FeZn-NC in Comparative Example 3 and Zn-NC in Comparative Example 1. Implementation
[0030] The present invention is further described in detail below with reference to the accompanying drawings.
[0031] Example 1: Synthesis of MnZn-NC
[0032] 1314 mg of 2-methylimidazole and 1190 mg of zinc nitrate hexahydrate were weighed and dissolved in 25 mL and 20 mL of methanol respectively. After ultrasonication until completely dissolved, 2-methylimidazole methanol solution and zinc nitrate hexahydrate methanol solution were obtained. Under stirring conditions at room temperature, 2-methylimidazole methanol solution, zinc nitrate hexahydrate methanol solution and 0.05 mmol of manganese acetylacetonate were mixed at the same time, and the reaction was stirred at room temperature for 4 h. The product was centrifugally washed three times with methanol, and the three precipitates were combined and placed in a vacuum drying oven at 60 °C for 6 h. The dried MnZn-ZIF-8 was evenly ground and spread on the magnetic boat, and placed in the middle of the quartz tube of the tubular furnace to form a closed system. After inert gas (N2) was continuously passed for 30 min, the tubular furnace was heated to 900 °C (heating rate of 5 °C / min) and maintained at this temperature for 2 h. After the calcination process was completed, the temperature dropped below 40 °C and it was taken out to obtain the catalyst MnZn-NC.
[0033] Example 2: Synthesis of MnZn-NC
[0034] 0.05 mmol of manganese acetylacetonate was added, and the mixture was stirred at room temperature for 3 h. Other conditions were the same as those in Example 1.
[0035] Example 3: Synthesis of MnZn-NC
[0036] The temperature of the tube furnace was raised to 800° C., and other conditions were the same as those in Example 1.
[0037] Figure 1 This is an electron microscope image of the MnZn-NC prepared in Example 1. It can be seen that the MnZn-NC is in the shape of a rhombic dodecahedron, with a size between 300-600 nm, and no obvious metal particles are observed.
[0038] Figure 2 This is the spherical aberration corrected high-angle annular dark field scanning transmission electron microscope HAADF-STEM image of MnZn-NC prepared in Example 1. It can be seen that under the dark field spherical aberration electron microscope, the Mn and Zn atoms with higher atomic numbers on the MnZn-NC appear as brighter points compared to the nitrogen-doped carbon carrier, indicating that they are all distributed on the carrier in the form of single atoms, and no other particles or other substances are found.
[0039] Figure 3 This is the X-ray diffraction pattern of MnZn-NC prepared in Example 1. It can be seen that there is a broad shoulder peak in the range of 20-30°. By comparison, this peak belongs to the diffraction peak of graphite carbon. Apart from this, no other obvious characteristic peaks are found, indicating that the MnZn-NC catalyst material does not contain other impurities such as metal particles and metal oxides.
[0040] Comparative Example 1: Synthesis of Zn-NC
[0041] 1314 mg of 2-methylimidazole and 1190 mg of zinc nitrate hexahydrate were weighed and dissolved in 25 mL and 20 mL of methanol respectively. After ultrasonication until completely dissolved, 2-methylimidazole methanol solution and zinc nitrate hexahydrate methanol solution were obtained. Under stirring conditions at room temperature, 2-methylimidazole methanol solution and zinc nitrate hexahydrate methanol solution were mixed at the same time, and the reaction was stirred at room temperature for 4 hours. After the product was centrifuged and washed three times with methanol, the three precipitates were combined and placed in a vacuum drying oven at 60 °C for 6 hours. After the dried ZIF-8 was evenly ground and spread on the magnetic boat, it was placed in the middle of the quartz tube of the tubular furnace to form a closed system. After inert gas (N2) was continuously passed for 30 minutes, the tubular furnace was heated to 900 °C (heating rate of 5 °C / min) and maintained at this temperature for 2 hours. After the calcination process was completed, when the temperature dropped below 40 °C, it was taken out to obtain the catalyst Zn-NC.
[0042] Comparative Example 2: Synthesis of Mn-NC
[0043] Weigh 200 mg of SiO2 microspheres and dissolve them in 145 mL of deionized water. Weigh 18.2 mg of hexadecyltrimethylammonium bromide (CTAB). Stir the reaction thoroughly at room temperature for 30 min to allow CTAB to adsorb on the surface of the SiO2 spheres. Then add 0.5 mL of NH3.H2O, 125 mg of resorcinol, and 175 µL of formaldehyde. Stir the reaction thoroughly at room temperature for 1 h, then add 47.5 mg of melamine and 175 µL of formaldehyde. Continue to stir the reaction thoroughly for 1 h. Then add 0.025 mmol of Mn(NO3)2 and stir the reaction for 2 h. After the product was washed three times by centrifugation with ethanol, the three precipitates were combined and placed in a vacuum drying oven at 60 °C for 6 h. The dried material was placed in the middle of the quartz tube of the tube furnace to form a closed system. After the inert gas (N2) was continuously passed for 30 min, the temperature was raised to 900 °C (heating rate was 5 °C / min) and maintained at this temperature for 2 h. After the calcination process, when the temperature drops below 40 °C, the material is taken out and placed in a 25 mL round-bottom flask, 20 mL of 0.1 mol / L NaOH is added, and refluxed at 80 °C for 4 h. The refluxed material is centrifugally washed three times with deionized water, and the three precipitates are combined and placed in a vacuum drying oven at 60 °C for 6 h. Weigh the dried material, add 8 mL of 0.1 mol / L H2SO4 solution for every 100 mg, stir and react at 80 °C for 12 h, and the stirred material is centrifugally washed with deionized water until the solution is neutral. The precipitates are combined and placed in a vacuum drying oven at 60 °C for 6 h to obtain the final Mn-NC catalyst material.
[0044] Comparative Example 3: Synthesis of FeZn-NC
[0045] 1314 mg 2-methylimidazole and 1190 mg zinc nitrate hexahydrate were weighed and dissolved in 25 mL and 20 mL methanol, respectively. After ultrasonication until completely dissolved, 2-methylimidazole methanol solution and zinc nitrate hexahydrate methanol solution were obtained. The 2-methylimidazole methanol solution, zinc nitrate hexahydrate methanol solution and 0.05 mmol ferric acetylacetonate were mixed at room temperature under stirring conditions. After fully stirring and reacting for 4 h at room temperature, the product was centrifugally washed three times with methanol, and the three precipitates were combined and placed in a vacuum drying oven at 60 °C for 6 h. The dried FeZn-ZIF-8 was evenly ground and spread on a magnetic boat, and placed in the middle of the quartz tube of a tubular furnace to form a closed system. After that, an inert gas (N2) was continuously passed for 30 min, and the tubular furnace was heated to 900 °C (heating rate of 5 °C / min) and maintained at this temperature for 2 h. After the calcination was completed, the temperature dropped below 40 °C and it was taken out to obtain the catalyst Fe / Zn-NC.
[0046] Comparative Example 4: Synthesis of CoZn-NC
[0047] The synthetic steps are the same as those of Comparative Example 3, except that the ferric acetylacetonate is replaced with an equal amount of cobalt acetylacetonate.
[0048] Comparative Example 5: Synthesis of NiZn-NC
[0049] The synthesis steps are the same as those of Comparative Example 3, except that the ferric acetylacetonate is replaced with an equal amount of nickel acetylacetonate.
[0050] Comparative Example 6: Synthesis of CuZn-NC
[0051] The synthetic steps are the same as those of Comparative Example 2, except that the ferric acetylacetonate is replaced with an equal amount of copper acetylacetonate.
[0052] Figure 5 The X-ray photoelectron spectra of the Zn 2p orbitals of the MnZn-NC prepared in Example 1 of the present invention, the FeZn-NC in Comparative Example 3 and the Zn-NC in Comparative Example 1 show that the Zn 2p electronic states of the MnZn-NC, FeZn-NC and Zn-NC are significantly different. The Zn 2p standard spectrum can be analytically fitted into two Zn 2p orbitals. 1 / 2 and 2p 3 / 2By comparing the binding energy of Zn 2P orbitals in MnZn-NC, Zn-NC, and FeZn-NC, it was found that: Compared with the Zn 2P orbitals of Zn-NC, the Zn 2P in MnZn-NC moves to the high field, indicating that the oxidation state of the Zn element increases and the Lewis acidity increases; the Zn2P in FeZn-NC moves to the low field, the oxidation state of the Zn element decreases, and the Lewis acidity decreases. XPS characterization shows that the introduction of different transition metal elements can regulate the electronic configuration of Zn, making the MnZn-NC catalyst more active in catalyzing cycloaddition reactions.
[0053] Application Examples
[0054] The bimetallic single atom catalyst was applied to the carbon dioxide cycloaddition reaction to detect the catalytic performance of the bimetallic single atom catalyst, specifically:
[0055] The catalysts prepared in Examples 1-3 and Comparative Examples 1-6 were used in the carbon dioxide cycloaddition reaction, and the specific process was as follows:
[0056] Take 65 mg of catalyst, 2 mL of substrate styrene oxide, and 65 mg of tetrabutylammonium bromide and add them to a 10 mL Shrek tube; then put the Shrek tube into an ultrasonic cleaner to evenly disperse the components through ultrasonic action. Insert the vent needle below the reaction liquid surface and pass carbon dioxide gas for 30 min (gas flow rate: 30 mL / min) to exhaust the air in the system and activate the system. After 30 min, place a condenser on the upper end of the Shrek tube and put on a balloon filled with carbon dioxide gas (gas flow rate 100 mL / min, pass 30 s). Finally, place the reaction device on a digital temperature-controlled heating stirrer, the reaction temperature is 90 °C, and after 12 h of reaction, it is cooled to room temperature. Use a syringe to aspirate the reaction liquid, use a filter membrane to separate the catalyst from the reaction liquid, and the liquid product is obtained. The product content is analyzed by gas chromatography, as shown in Table 1:
[0057] The conversion rate is calculated as follows:
[0058] Conversion rate % = styrene oxide consumption before and after the reaction / styrene oxide feed amount × 100%;
[0059] The selectivity is calculated as follows:
[0060] Selectivity % = molar amount of styrene carbonate / total molar amount of styrene oxide consumption × 100%.
[0061] Table 1 Conversion rate and selectivity of the catalysts prepared in Examples 1-3 and Comparative Example 6 for carbon dioxide cycloaddition
[0062]
[0063] It can be seen from the above table that compared with comparative examples 1-2, the conversion rate of embodiments 1-3 is better, indicating that after loading the bimetallic, the synergistic effect between metallic manganese and zinc can efficiently catalyze the cycloaddition reaction of carbon dioxide and epoxy compounds; compared with comparative examples 3-6, the conversion rate of embodiments 1-3 is better, indicating that compared with other transition metals, the MnZn-NC bimetallic single atom catalyst prepared by limiting manganese metal has more excellent reaction activity.
[0064] In the application example, the filter membrane separates the catalyst from the reaction solution, and the MnZn-NC bimetallic single atom catalyst of Examples 1-3 obtained by separation can be reused after washing and drying.
[0065] Figure 4 The performance results of multiple cycles of the cycloaddition of styrene oxide and carbon dioxide catalyzed by MnZn-NC in Example 1 show that MnZn-NC still has 94.3% of the catalytic performance after 5 cycles, indicating that the MnZn-NC catalyst has relatively good structural stability.
[0066] The catalyst prepared in Example 1 was used in different carbon dioxide cycloaddition reactions, that is, different epoxide substrates were used. The specific process was as follows: 65 mg of catalyst, 20 mmol of substrate epoxide, and 65 mg of tetrabutylammonium bromide were added to a 10 mL Shrek tube; the Shrek tube was then placed in an ultrasonic cleaner to evenly disperse the components by ultrasonic action. The venting needle was inserted below the reaction liquid surface, and carbon dioxide gas was passed for 30 min (gas flow rate: 30 mL / min) to evacuate the air in the system and activate the system. After 30 min, a condenser was placed on the upper end of the Shrek tube, and a balloon filled with carbon dioxide gas was put on (gas flow rate 100 mL / min, 30 s). Finally, the reaction device was placed on a digital temperature-controlled heating stirrer, the reaction temperature was 90 ° C, and after 12 h of reaction, it was cooled to room temperature. The reaction solution was sucked out with a needle tube, and the catalyst was separated from the reaction solution with a filter membrane. The liquid product obtained was analyzed by gas chromatography for product content, as shown in Table 2:
[0067] Table 2 Conversion rate and selectivity of the catalyst in Example 1 for the cycloaddition reaction of different substrates with carbon dioxide
[0068]
[0069] As can be seen from the above table, MnZn-NC bimetallic single atoms can be used for the reaction of a variety of epoxide substrates with CO2, and all have excellent catalytic effects, indicating that the prepared bimetallic single atom catalyst has good universality.
[0070] In addition to the above embodiments, the present invention also includes other implementation modes. Any technical solutions formed by equivalent transformation or equivalent replacement should fall within the protection scope of the claims of the present invention.
Claims
1. Application of a bimetallic single atom catalyst for carbon dioxide cycloaddition reaction, Features: Using a bimetallic single atom catalyst as the main catalyst and tetrabutylammonium bromide as the co-catalyst, carbon dioxide reacts with an epoxide under normal pressure. The bimetallic single-atom catalyst uses a nitrogen-doped carbon material derived from a zeolite imidazolate framework material ZIF-8 as a carrier, and metal manganese and zinc as two metal single-atom components are loaded on the nitrogen-doped carbon material; The loading amount of metal manganese single atom on the bimetallic single atom catalyst is 0.09 wt.%; The loading amount of the metal zinc single atom on the bimetallic single atom catalyst is 9.1wt.%; The bimetallic single-atom catalyst is prepared by the following preparation method: 1) dissolving zinc nitrate and 2-methylimidazole in methanol to obtain a zinc nitrate methanol solution and a 2-methylimidazole methanol solution respectively, adding the zinc nitrate methanol solution, the 2-methylimidazole methanol solution and a metal precursor manganese acetylacetonate at the same time under stirring at room temperature, stirring at room temperature, centrifuging, washing and vacuum drying to obtain a mixture; 2) The mixture is heat treated by high temperature pyrolysis in an inert atmosphere to obtain a bimetallic single atom catalyst.
2. Use of the bimetallic single atom catalyst for carbon dioxide cycloaddition reaction according to claim 1, Features: The stirring time at room temperature in step 1) is 2 to 4 hours.
3. Use of the bimetallic single atom catalyst for carbon dioxide cycloaddition reaction according to claim 1, Features: The centrifugal washing and vacuum drying in step 1) are specifically as follows: after centrifugal washing with methanol for 3 times, the three precipitates are combined and placed in a vacuum drying oven at 60°C for 6 hours.
4. Use of the bimetallic single atom catalyst for carbon dioxide cycloaddition reaction according to claim 1, Features: The heat treatment temperature in step 2) is 700 ~ 1000 ° C.
5. Use of the bimetallic single atom catalyst for carbon dioxide cycloaddition reaction according to claim 1, Features: The epoxy compound is any one of propylene oxide, epichlorohydrin, phenyl glycidyl ether, styrene oxide and glycidol.
Citation Information
Patent Citations
Immobilized ion liquid catalyst used for carbon dioxide cycloaddition reaction and preparation method of supported ion liquid catalyst
CN106732768A
Catalyst for efficiently catalyzing cycloaddition reaction of carbon dioxide and epoxide
CN107096569A
Organic porous polymer for catalyzing cycloaddition of epoxide and carbon dioxide
CN113912805A
Preparation method of metal monatomic site catalyst
CN107626294A
Preparation method and application of heterogeneous Schiff base catalyst
CN109675634A
Cited By
Preparation method of monatomic catalyst as well as product and application of monatomic catalyst
CN120054588A
